2017
DOI: 10.1094/pdis-04-16-0464-re
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fungicides and Spray Application Interval on Controlling Marssonina Blotch of Apple in the Loess Plateau Region of China

Abstract: Marssonina blotch, caused by the fungus Marssonina coronariae, is a serious foliar disease on apple in East Asia as well as in other moist temperate regions in Asia, Europe, and South America. Several fungicides were investigated for their toxicity to mycelial growth and conidial germination of the pathogen in vitro. Tebuconazole, kresoxim-methyl, hexaconazole, propiconazole, and a mixture of tebuconazole and benziothiazolinone sharply inhibited mycelial growth but had less effect on conidial germination. Fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…High control efficacy of DIF has been reported in several ascomycetes such as Phacidiopycnis spp., Venturia inaequalis, Colletotrichum spp., Marssonina coronaria, Alternaria spp., and Fusarium spp. ( Munkvold and O’Mara, 2002 ; Villani et al, 2015 ; Fonseka and Gudmestad, 2016 ; Cao et al, 2017 ; Dang et al, 2017 ; Ali et al, 2018 ) and the basidiomycete Rhizoctonia solani ( Bartholomäus et al, 2017 ). Given the widespread occurrence of resistance to two of the three current postharvest fungicides and the stringent limitations to new postharvest fungicides registration, DIF could be a valuable additional tool to manage blue mold of pome fruit in the years to come if used appropriately and if its efficacy against other major postharvest diseases is proven.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High control efficacy of DIF has been reported in several ascomycetes such as Phacidiopycnis spp., Venturia inaequalis, Colletotrichum spp., Marssonina coronaria, Alternaria spp., and Fusarium spp. ( Munkvold and O’Mara, 2002 ; Villani et al, 2015 ; Fonseka and Gudmestad, 2016 ; Cao et al, 2017 ; Dang et al, 2017 ; Ali et al, 2018 ) and the basidiomycete Rhizoctonia solani ( Bartholomäus et al, 2017 ). Given the widespread occurrence of resistance to two of the three current postharvest fungicides and the stringent limitations to new postharvest fungicides registration, DIF could be a valuable additional tool to manage blue mold of pome fruit in the years to come if used appropriately and if its efficacy against other major postharvest diseases is proven.…”
Section: Discussionmentioning
confidence: 99%
“…It is pre-mixed with FDL and commercially available as Academy™ (Syngenta Crop Protection). Difenoconazole (DIF) has a systemic activity and broad-spectrum antifungal potency as shown recently ( Hof, 2001 ; Fonseka and Gudmestad, 2016 ; Bartholomäus et al, 2017 ; Dang et al, 2017 ; Jurick et al, 2017 ; Koehler and Shew, 2018 ; Ali et al, 2018 ). DMIs, such as DIF, target the sterol 14α-Demethylase Cytochrome P450 ( CYP51 ), an essential component of fungal membrane sterols required for a proper membrane functioning ( Rodriguez et al, 1985 ; Joseph-Horne and Hollomon, 1997 ).…”
Section: Introductionmentioning
confidence: 90%
“…20 Studies related to BIT mainly focused on synthetic method, control efficiency on target organisms, and instrumental analysis method of residue detection in crops (cucumber, wheat, and tobacco) and soil. [15][16][17]21,22 Previous investigation of our group found BIT residues in citrus, and the results showed BIT poses certain dietary exposure risk to human. 23 United States Environmental Protection Agency (EPA) have reported the application amount of BIT to crops is 0.02 lbs per acre.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the absence of resistant cultivars, fungicides are required for PLF management (Bala et al, 2001). Earlier studies demonstrated that chemical fungicides are effective at managing PLF (Dang et al, 2017; Kumar & Sharma, 2014; Lee et al, 2009; Verma & Khosla, 2018), but repeated use of chemical fungicides may result in problems such as fungicide resistance and high residue levels in fruit (Tanaka et al, 2000). Therefore, there is a clear need for environmentally friendly, safe fungicides with diverse modes of action.…”
Section: Introductionmentioning
confidence: 99%